2016
DOI: 10.5194/tc-10-1003-2016
|View full text |Cite
|
Sign up to set email alerts
|

Past ice-sheet behaviour: retreat scenarios and changing controls in the Ross Sea, Antarctica

Abstract: Abstract. Studying the history of ice-sheet behaviour in the Ross Sea, Antarctica's largest drainage basin can improve our understanding of patterns and controls on marinebased ice-sheet dynamics and provide constraints for numerical ice-sheet models. Newly collected high-resolution multibeam bathymetry data, combined with two decades of legacy multibeam and seismic data, are used to map glacial landforms and reconstruct palaeo ice-sheet drainage.During the Last Glacial Maximum, grounded ice reached the contin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
174
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(191 citation statements)
references
References 107 publications
16
174
1
Order By: Relevance
“…Vulnerability of WAIS to future warming can be assessed by investigating how it has responded to different climate regimes in the past. Unfortunately, geologic evidence of the past size and extent of Antarctic ice sheets is spatially sparse, tends to have large chronological uncertainty, and is sometimes 10 contradictory (Whitehouse et al, 2012;Anderson et al, 2014;Bentley et al, 2014;Clark and Tarasov, 2014;Halberstadt et al, 2016;McKay et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulnerability of WAIS to future warming can be assessed by investigating how it has responded to different climate regimes in the past. Unfortunately, geologic evidence of the past size and extent of Antarctic ice sheets is spatially sparse, tends to have large chronological uncertainty, and is sometimes 10 contradictory (Whitehouse et al, 2012;Anderson et al, 2014;Bentley et al, 2014;Clark and Tarasov, 2014;Halberstadt et al, 2016;McKay et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Ross Embayment is the largest drainage of WAIS, both in terms of area and mass loss (Halberstadt et al, 2016). The glacial history of WAIS in the Ross Sea has been speculated about since Captain James Ross first mapped its edge in 1841-1842, followed by the first geologic studies of the region during the Discovery, Nimrod, and Terra Nova expeditions (Scott, 1907;15 David et al, 1910-11;Debenham, 1921).…”
Section: Introductionmentioning
confidence: 99%
“…Lateral drag increases as the width narrows, which may lead to ice stabilization that could result in transverse features, based on the amount of sediment flux and duration of the stillstand (Howat and Domack, 2003;Dowdeswell and Vasquez, 2013). Transverse-to-flow features in the Ross Sea and Weddell Sea (Halberstadt et al, 2016;Campo et al, 2017) are larger than the GZW and moraines identified in this study and are the result of a much larger ice flow system. Therefore, width may play a major role in confined flow, e.g.…”
Section: Geometry Of Baysmentioning
confidence: 59%
“…4, 5). The geometry of these transverse ridges is similar to much larger GZW in the Ross Sea (Halberstadt et al, 2016) and the Weddell Sea (Campo et al, 2017). The size of the GZW has been correlated with the length of ice stability (Alley et al, 2007;Dowdeswell and Vasquez, 2013;Batchelor and Dowdeswell, 2015), a larger GZW imply a longer period of ice stability.…”
Section: Ice-marginal Landforms Large Transverse Ridges: Grounding Zomentioning
confidence: 66%
“…Topographical base map from USGS (1967) coastal ice morphology, surface gradients and surface elevations were probably broadly similar to today (e.g. Denton and Hughes 2002; Anderson et al 2014;Halberstadt et al 2016). Exposure of the bedrock ridges at Harrow Peaks took place only a few thousand years prior to the timing of grounding line retreating to the south of Wood Bay.…”
Section: Environmental Implicationsmentioning
confidence: 99%